Hard and Tough Epoxy Resins Modified with Thermosetting Materials - Abdullah, H . M . (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
Epoxy resins were modified by some thermosetting materials using unsaturated polyesters which were cured with styrene , MMA ,and MA . When unsaturated Polyester ( as thermosetting material ) was used , and cured with styrene showed better results than acrylic monomers . Thermal stability rised on modification of epoxy resins with unsaturated polyester . The new formulation had converted the epoxy resin from hard brittle material to hard and tough material . Thermal analysis were studied using ( DSC ) and physicomechanical characteristics were measured .